Respuesta :

Answer:

To solve by using the elimination method you need to get one of the variables the same number (the x or y)

We are going to use the y because one is negative and the other is positive

-4x-15y=-17

-x+5y=-13

To get like terms on the y we are going to multiply the bottom equation by 3

(-x+5y=-13) *3

Your new equation would be

-3x+15y=-39 (now your equations look like this:

-4x-15y=-17

-3x+15y=-39

Now you can eliminate the y's by adding, so lets now add the two equations vertically

-4x-15y=-17

-3x+15y=-39

-4x+ -3x= -7x

-15y+15y=0

-17+ -39= -56

Your new equation is:

-7x=-56 (divide each side by a -7 to get x by itself)

x=8

Now you want to plug x in for the bottom equation to find your y so:

-(8) + 5y= -13

-8+5y=-13 (add 8 to both sides)

5y=-5 (divide each side by 5)

y=-1

Your answer is

(8, -1)

Hope this helps ;)

Step-by-step explanation: